Operational Management Plan Infinity Workspace - Isworo, Joko; Indradewa, Rhian; Abadi, Ferryal; Iskandar, Muhammad Dhafi (Syntax Corporation, 2025)
The digital economy transformation has significantly increased the demand for flexible workspaces, particularly in Jakarta as a business hub. Coworking spaces are now perceived not merely as office alternatives but as strategic platforms supporting productivity, innovation, and collaboration. This study aims to develop an operational plan for PT. Infinity Workspace (IWS), a coworking space provider with three strategic locations in South, Central, and West Jakarta. Using a descriptive qualitative method, the study examines business establishment procedures, operational objectives, service design, quality management, and financial projections. The findings reveal that IWS implements phased operational strategies: short-term standardization, medium-term service improvement and technology integration, and long-term sustainable innovation. The service design emphasizes differentiation through modern interiors, app-based access, and a transparent service blueprint. Financially, detailed capital expenditure, pre-operational, and operational cost planning ensure efficiency and sustainability. By integrating location strategy, service quality, technology, and financial management, IWS is positioned as a competitive player in Jakarta’s coworking space industry.